PROFILE OF STUDENT MATHEMATICAL PROBLEM SOLVING BASED ON COGNITIVE STYLE IN GRADE VIII - Athifa Musyafani; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2018)
The ability to solve problems is one of the 21st-century skills that students master. In school, there are various cognitive styles in solving math problems. So it is necessary to describe the problem-solving skills of students of State Junior High School (SMP Negeri) 3 Kasihan Bantul class VIII in terms of the cognitive style of field-dependent (FD) and field independent (FI) of the academic year 2017/2018. Â This research is qualitative descriptive research. The subject of research consists of 2 students whose cognitive style FD and two students cognitive FI style. The instrument used in this research consists of the main instrument that is self-researcher. The auxiliary instruments are Group Embedded Figure Test (GEFT) and Problem Solving Testing (TKPM). For data collection techniques used are GEFT, TKPM, and interviews. To obtain data consistency, used technique triangulation. Data analysis techniques include data reduction, data presentation, and conclusions. The results showed that the subject of FD tends to think globally in solving the problem. Subjects have used three problem-solving indicators: understanding the problem by repeated reading, planning by analyzing, implementing plans that have been prepared to get the results of completion, and drawing conclusions. At the same time, the subject of FI is more analytical in solving the problem. The subject has used three troubleshooting indicators, understood the problem by repeated reading, drafted a settlement plan from the information obtained, executed the plan developed to get the result of completion, and drew conclusions. The subject of FD and FI equally did not re-examine the answer.